Effect of bosentan on lipid peroxidation and electroencephalography in rats with induced cerebral ischaemia-reperfusion - Berilgen, M. S.; Kaplan, M.; Akgun, B.; Sari, A.; Ozdemir, H.; Demir, C. F. (Springer Heidelberg, 2012)
[Abstract Not Available]
22nd Meeting of the European-Neurological-Society -- JUN 09-12, 2012 -- Prague, CZECH REPUBLIC